Transparent Soap with Dihydroxystearic Acid (DHSA) - A. Norashikin Ahmad (Universiti Sains Islam Malaysia, 2024)
A conventional transparent soap is prepared by combining fatty acid-based soap with polyol or combination of polyols (i.e. sugars, sorbitol and glycerine) and glycols (i.e. propylene glycol and ethylene glycol) to impart transparency to the soap. In a new method developed by MPOB, palm-based transparent soap with dihydroxystearic acid (DHSA) was successfully developed. DHSA is a dihydroxy saturated fatty acid derived from palm oleic acid. The synthesis of DHSA was also carried out by MPOB and the process to produce the DHSA has been filed for patent application (PI9804456). The addition of DHSA, either crude or purified, in the transparent soap can improve its transparency. The transparency enhancement by DHSA is a lot better than the results obtained from the adding of mono hydroxyl acid. Other advantages of the transparent soap with DHSA are that they have good foaming power and detergency as compared to commercially available transparent soaps. Besides, the soap with DHSA is safe to be used with no skin irritation. The technology to formulate the transparent soap with DHSA has also been filed for patent application (PI 20082058).